The Professional Leadership Model of English Major Teachers in Universities Under Liaoning Province - Ying, Lian; Chanphong , Somsak; Howattanakul , Sutida (Journal of Roi Kaensarn Academi, 2024)
The objectives of this research were:(1) to explore the components and indicators of the professional leadership of English major teachers in universities under Liaoning Province, (2) to verify the components of the professional leadership model of English major teachers in universities under Liaoning Province, and (3) to propose the guidelines for improving the professional leadership of English major teachers in universities under Liaoning Province. The research was a mixed methodology research. Population was English major teachers and administrator, totaling 864 people. The sample size was obtained by stratified random sampling, totaling 268 people. The key informants were 8 people, obtained by purposive sampling method. The instruments used for data collection were semi-interview, three-level scale questionnaire and focus group discussion form. The statistics used for data analysis were frequency, percentage, mean, standard deviation, confirmatory factor analysis and content analysis. The research findings revealed that: (1) the professional leadership of English major teachers in universities under Liaoning Province consisted 5 components and 50 indicators, which were personality inspiration, teaching leading force, academic foresight, learning growth and organizational cohesion, (2) the model of professional leadership of English major teachers in universities under Liaoning Province fit with the empirical data for all indicators, and(3)15guidelines for improving the professional leadership of English major teachers in universities under Liaoning Province were proposed.